1997
DOI: 10.1002/(sici)1097-0142(19971225)81:6<365::aid-cncr11>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Effusion cytology of esophageal carcinoma

Abstract: known esophageal carcinoma, 37 of whom underwent resection.RESULTS. Seventeen specimens were from 10 patients with squamous cell carci- Esophageal carcinoma is one of the most common carcinomas worldwide, and the incidence of esophageal adenocarcinoma is increasing.1 Despite the close anatomic relationship to the pleural and pericardial spaces and frequent high stage disease, malignant effusions due to esophageal carcinoma appear to be rare. Although malignant effusions due to carcinomas from the gastrointest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…We included carcinomas from these 3 sites because they are the most common carcinomas in malignant pleural effusions . However, metastases to the pleura from numerous other sites, including prostate, upper gastrointestinal tract, colorectal, and pancreatic primary tumors are encountered. Although the differential diagnosis for AE1/AE3‐positive and WT1–negative cells consists mostly of nonovarian carcinomas, other keratin‐positive neoplasms such as epithelioid sarcoma have been reported in pleural fluids .…”
Section: Discussionmentioning
confidence: 99%
“…We included carcinomas from these 3 sites because they are the most common carcinomas in malignant pleural effusions . However, metastases to the pleura from numerous other sites, including prostate, upper gastrointestinal tract, colorectal, and pancreatic primary tumors are encountered. Although the differential diagnosis for AE1/AE3‐positive and WT1–negative cells consists mostly of nonovarian carcinomas, other keratin‐positive neoplasms such as epithelioid sarcoma have been reported in pleural fluids .…”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported that the incidence of cytological positivity of pleural lavage specimens was significantly higher in adenocarcinoma than in squamous cell carcinoma. 7,9 In this series, all patients had squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 64%
“…7,8 There have been few reports, however, on the cytological findings for pleural lavage fluid in esophageal carcinoma. 9 The aim of this study was to determine whether intraoperative cytological examination of pleural lavage fluid could be used as an indicator of recurrence and patient prognosis in esophageal carcinoma.…”
mentioning
confidence: 99%
“…[12] Some other rare causes of pleural effusion with squamous cells have been described in the literature. Malignant pleural effusions can rarely be seen in patients with metastatic squamous cell carcinoma of the esophagus,[13] cervix[14] or penis. Benign squamous cells have also been described in an instance of rupture of a mediastinal benign cystic teratoma into a pleural space.…”
Section: Discussionmentioning
confidence: 99%